Environmental Safety of the Sewage Disposal by the Sewerage Pipelines. (2016) - Iurchenko, Valentina; Lebedeva, Elena; Brigada, Elena
Abstract: The concentration of hydrogen sulfide and other gases in the sewerage pipelines of the Kharkov city was measured during the experimental studies. Based on the obtained figures the emission of hydrogen sulphide through the sewer shafts in urban environment and its dispersion in the atmosphere of specific urban areas were estimated. The interface of the page for the monitored indicators of the environmental safety and operational reliability of specific areas of the water disposal pipelines was developed. It can be used for the geographic information system of the urban sewer networks.